PB 21 Female superiority in "Mindreading from the Eyes" is diminished after menopause – results from the LIFE-adult study. Issue 10 (October 2017) - Kynast, J.; Quinque, E.M.; Polyakova, M.; Luck, T.; Riedel-Heller, S.G.; Baron-Cohen, S.; Villringer, A.; Schroeter, M.L.
Abstract : Background: Theory of Mind (ToM) is essential for successful social interactions, as it enables the understanding of another person's mental state and the prediction of future behavior. As affective information is conveyed through gaze, the "Reading the Mind in the Eyes" Test (RMET) is a frequently used tool for the assessment of ToM. This is the first study to investigate the effects of sex on a wide age range (19–79 years) in a large, population-based German sample. As RMET scores have been shown to be sensitive to hormonal changes, the sex effect before and after menopause (cut-off age: 45) was of particular interest. Methods: The sample comprised 1603 participants of the LIFE study. We investigated the effects of age and sex on RMET performance by applying linear regression, correcting for verbal ability. The size of the effects of sex and age were estimated using Hedges g. Effect sizes for the age groups below and above 45 years were analyzed with respect to male-female differences. Results: We found significant effects of sex and age on RMET performance. Older adults presented lower accuracy rates compared to younger adults. Effects remained stable when considering other cognitive abilities. Women outperformed men before the age of 45, while the male-female performance difference was reduced in individuals above 45 years of age. Discussion: Both men and women show a decline in affective ToM with increasing age in this comprehensive community-dwelling study. Thus, older adults may have particular problems inferring complex emotional content from gaze. Data suggest that female superiority in mindreading abilities is diminished after menopause, presumably due to changes in the concentration of circulating hormones.